Resveratrol: A Vital Therapeutic Agent with Multiple Health Benefits - Kaur, Arshpreet; Tiwari, Ruchi; Tiwari, Gaurav; Ramachandran, Vadivelan (Drug Research, 2021)
Resveratrol (RSV), the most effective stilbene phytoalexin synthesized naturally or induced in plants as part of their defense mechanism, is a key component of natural phenolic compounds and is being considered as a treatment option for a variety of diseases. RSV was discovered in the skin of red grapes, mulberries, peanuts, pines, and Polygonum cuspidatum weed root extracts. It was first extracted from white hellebore (Veratrum grandiflorum O. Loes) roots in 1940, then from Polygonum cuspidatum roots in 1963. However, RSV’s use as a drug is limited due to its initial conformational strength and poor stability. The research focused on a set of RSV biological activity data. RSV has been the subject of growing concern, despite its wide range of biological and therapeutic applications. According to the literature, RSV has antioxidant, anti-cancer, cardioprotective, neuroprotective, anti- inflammatory, anti-microbial, immunomodulatory, and radioprotective properties. The current analysis summarized biological applications of RSV, their mechanisms of action, and recent scientific development in the area of their delivery. It is possible to infer that RSV has many effects on infected cells’ cellular functions.
Keywords: RSV; Therapeutic properties; Mechanism of action; Side effects; Future prospects